2008
DOI: 10.1371/journal.ppat.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Proteins A52 and B14 Share a Bcl-2–Like Fold but Have Evolved to Inhibit NF-κB rather than Apoptosis

Abstract: Vaccinia virus (VACV), the prototype poxvirus, encodes numerous proteins that modulate the host response to infection. Two such proteins, B14 and A52, act inside infected cells to inhibit activation of NF-κB, thereby blocking the production of pro-inflammatory cytokines. We have solved the crystal structures of A52 and B14 at 1.9 Å and 2.7 Å resolution, respectively. Strikingly, both these proteins adopt a Bcl-2–like fold despite sharing no significant sequence similarity with other viral or cellular Bcl-2–lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
202
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(211 citation statements)
references
References 70 publications
7
202
1
1
Order By: Relevance
“…The A52, K7, and B15 early proteins, members of the B-cell lymphoma-2 family (31,32), are involved in suppression of host immune responses (2). During infection, A52 and K7 interact with TNF receptor-associated factor 6 and inhibit its kinase activation capacity (24,33), whereas B15 binds the IκB kinase complex to inhibit IκBα phosphorylation and degradation (20).…”
Section: Discussionmentioning
confidence: 99%
“…The A52, K7, and B15 early proteins, members of the B-cell lymphoma-2 family (31,32), are involved in suppression of host immune responses (2). During infection, A52 and K7 interact with TNF receptor-associated factor 6 and inhibit its kinase activation capacity (24,33), whereas B15 binds the IκB kinase complex to inhibit IκBα phosphorylation and degradation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was assumed that A46 would adopt a TIR fold and bind to TIR proteins via homotypic interactions. However, the crystal structures of A52 and B14, poxviral proteins related to A46, have been determined and shown that the proteins adopt a bcl-2-like fold, (39). Subsequent biophysical analysis of the purified C-terminal region of A46 (residues 81-230) revealed a highly ␣-helical structure, consistent with a bcl-2 fold (42).…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 itself and the TIR adaptor molecules Mal, MyD88, TRAM, and TRIF (32). A46 is predicted to form a Bcl-2-like fold, since the most significant structural homology was found with the VACV Bcl-2-like proteins A52 and B14 (38,39). Remarkably, VIPER, which is an 11 amino acid peptide derived from a surface patch of A46 predicted by the Bcl-2 model fused to a cell-penetrating delivery sequence, potently inhibited TLR4 responses, and associated with Mal and TRAM (38).…”
mentioning
confidence: 99%
“…25) even though it has no amino acid similarity to Bcl-2 or related proteins (26). A similar Bcl-2 fold has been also observed in two further VACV anti-inflammatory proteins B14 and K7 (18,(25)(26)(27) and by three anti-apoptotic VACV proteins, F1, M11, and N1 (27). The majority of these proteins form homodimers; however, the orientation of the monomers in the dimer can vary (25).…”
Section: Successful Vaccinia Virus (Vacv) Replication In the Host Reqmentioning
confidence: 99%